Social Rehabilitation of Children Through Basic Needs Services in Social Services Department, DKI Jakarta Province - Arifin, Ajruni Wulandestie; Fentiny Nugroho (International Journal of Education, Vocational and Social Science, 2025)
This study aims to describe the efforts and challenges of social rehabilitation services for children through basic needs fulfillment programs in the Special Capital Region of Jakarta, Indonesia. A qualitative approach with a descriptive research design was employed to provide a detailed and contextual understanding of the phenomenon. A total of 14 informants were selected using purposive sampling based on Neuman (2014), consisting of policymakers, social rehabilitation practitioners (foster parents, social workers, psychologists), and service recipients (institutionalized children and care leavers). The findings reveal that social rehabilitation efforts include: (1) capacity-building services for children through physical guidance, psychosocial support, spiritual guidance, life skills training, and self-actualization support; (2) services to fulfill children's rights such as basic needs provision, accessibility services, caregiving, social advocacy, and family tracing; (3) pre-termination guidance including career development and support for higher education; (4) institutional strengthening through child protection policies, multidisciplinary approaches, human resource management, and institutional standards; and (5) termination processes such as family reunification and referrals to other care institutions. These efforts have successfully met the goals of social rehabilitation as outlined by Wallace (2023), enabling children to reintegrate and participate in education, employment, and social roles within their families and communities.